Religious extremism and environmental hazards in Nigeria (2011)
Religion seems to be the only sphere devoid of regulatory agency in Nigeria. Even though there are religious associations, such as the Christian Association of Nigeria (CAN), Pentecostal Fellowship of Nigeria (PFN), Islamiyya, Ansar-ur-deen and Nasfat, to mention a few, they tend to be inactive in regulating the practice of religion by the adherents. This freedom has led to the conversion of shops and residential buildings to places of worship, thereby creating inconvenience for people through noisy environment. Therefore, the main focus of this paper is to advocate, among others, the need for the three tiers of government in Nigeria to come up with legislation to check the excesses or religious organizations, which has become a menace in this contemporary time.